Waste to wealth project with Mercu Resolution - Ajit, Azilah (2020)
Waste generation involves serious environmental pollution and degradation which consequently increased the environmental costs for its collection, treatment and disposal. Thus, the call for environmentally and economically sustainable growth is set out loud and simple. The present and future generations must therefore ensure that all resources are conserved, fully utilized and well managed. Various waste has been explored in this research such as municipal solid waste, fish waste and food waste. These wastes were utilized to become valuable resources and at the same time to reduce waste production. A total of seven studies have been done including biological degradation of municipal solid waste using mixed culture, production of biofertilizer using landfill leachate, oil extraction for a production of fatty acid from fish waste, fish feed production from fish waste, process simulation of anaerobic digestion process for biogas production from food waste, adsorbent from landfill sludge and finally, microwave irradiation and wet rendering to improve torrefaction of food waste. In conclusion, this research has successfully turned waste into wealth which later can be used for better future.